2008
DOI: 10.2478/v10042-008-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

An optimization of hematopoietic stem and progenitor cell isolation for scientific and clinical purposes by the application of a new parameter determining the hematopoietic graft efficacy.

Abstract: Abstract:The transplantation of hematopoietic stem and progenitor cells (HSPC) is an established lifesaving therapy. Bone marrow (BM), harvested from heparinized cadaveric organ donors, peripheral blood (PB) and cord blood (CB), are important sources of hematopoietic stem cells. HSPCs, which are used for transplantation purposes, are routinely evaluated in terms of number of mononuclear cells (MNCs), CD34 + MNCs count and viability. The efficacy of grafting is determined additionally in clonogenic tests in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Although number of HSPC plays a large part in determining the ultimate function of the graft, HSPC quality is likewise important for engraftment results. Graft characteristics, defined as the cell types found in the graft, their gene expression profiles, and their chemotactic reactivity to an SDF-1 gradient, all influence BM homing, engraftment, immune reconstitution and other post-transplant outcomes [153, 154]. …”
Section: Homingmentioning
confidence: 99%
“…Although number of HSPC plays a large part in determining the ultimate function of the graft, HSPC quality is likewise important for engraftment results. Graft characteristics, defined as the cell types found in the graft, their gene expression profiles, and their chemotactic reactivity to an SDF-1 gradient, all influence BM homing, engraftment, immune reconstitution and other post-transplant outcomes [153, 154]. …”
Section: Homingmentioning
confidence: 99%
“…In study focusing on the influence of different anticoagulants on chemotactic reactivity, the heparin has been considered the most suitable and safe anticoagulant for freshly isolated bone marrow hematopoietic stem and progenitor cells (BaUMERT et al, 2008). In this study, we have not found significant differences at harvest in terms of stem cell yield with both anticoagulants tested.…”
Section: Discussionmentioning
confidence: 53%
“…heparin and CPDa-1 are commonly used to harvest bone marrow (BaUMERT et al, 2008). heparin is a potent anticoagulant that has effects only in the presence of a plasma component termed heparincofactor (ROSENBERG, 1974), while the CPDa-1 is an adenine-containing preservative solution used to anticoagulant blood over a wider range (BEUTlER & WEST, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…BM aspirates were obtained from 15 patients in study group under local anesthesia from the posterior iliac crest within 24 hours after PCI. Mononuclear cells (MNCs) were obtained from harvested BM using centrifugation over Gradisol L (Polfa, Kutno, Poland) as described elsewhere [21]. Subsequently, the cells were incubated with anti-human antibodies conjugated with microbeads using a Lineage Depletion Kit (Myltenyi Biotec, Auburn, AL, USA) and isolated according to manufacturer's protocol as described [17], according to the good medical practice conditions.…”
Section: Preparation Of Autologous Bm-derived Lincellsmentioning
confidence: 99%